Effect of Subconscious Mind Programming and Suppressed Energy Releasing Through Ego Dissolving and Brain Unlocking on Entrepreneurship Character Building of Students at Institute of Economics IPWIJA - Martono, Besar Agung; Widyastuti, Titing (LPPM of STIMIK ESQ, 2017)
The purpose of this study was to analyze the effect of subconscious mind programming and suppressed energy releasing through ego dissolving and brain unlocking on the entrepreneurship character building of Students at Institutes of Economics IPWIJA.The model proposed in this study were tested using structural equation modeling. Data were collected from 310 samples students in institute of economics IPWIJA.The findings in this study, that brain unlocking, which has direct influence on the entrepreneurship character building of students. Subconscious mind programming directly influence suppressed energy releasing and positive thinking. The influence of subconscious mind programming on ego dissolving is mediated by suppressed energy releasing, while the effect on the suppressed energy releasing, positive thinking with ego dissolving. Ego dissolving and positive thinking directly influence the brain unlocking. The results of this study can be used as a useful tool for university leaders to strengthen decision-making aimed at improving the entrepreneurship character building of the students through subconscious mind programming, suppressed energy releasing, ego dissolving, positive thinking, and brain unlocking.